A Lot to Ask: Review Essay of Martha Nussbaum’s from Disgust to Humanity: Sexual Orientation and Constitutional Law - Case, Mary Anne (Columbia Journal of Gender and Law, 2010)
The title of Martha Nussbaum’s recent book From Disgust to Humanity: Sexual Orientation and Constitutional Law encapsulates well the book’s normative and descriptive claims. In Nussbaum’s descriptive account, the politics of disgust have been and remain at the root of all opposition to recognition of legal rights for homosexuals, whether the issue be sodomy laws, discrimination on the basis of sexual orientation, same-sex marriage or venues for public sex. Although she acknowledges that explicit appeals to disgust have declined in recent years, Nussbaum argues that disgust “has not gone away, it has gone underground.” In Nussbaum’s normative view, disgust not only should be ruled categorically out of bounds as a basis for law and policy, but must be thoroughly extirpated and replaced with a “politics of humanity” involving not only sympathy, imagination, and respect, but “something else, something closer to love.” From the moment early in its conception when she first sought my input on this new book, I had to confess myself troubled by its central claims, given my own very different take on the constitutional law of sexual orientation. As I shall explain in the remainder of this essay, it seems to me that From Disgust to Humanity descriptively accounts for too little and normatively asks for too much. Although I am a lawyer and not a moral philosopher, I shall begin by questioning the more philosophical, less legal aspect of Nussbaum’s normative claims before moving on to give an alternate account of developments in the law.